Pengaruh Talking to Babies Dan Murotal Al-Quran Terhadap Kestabilan Saturasi Oksigen Dan Frekuensi Nadi Pada Bayi Dengan Berat Badan Lahir Rendah - Mufidha Fairuuz Nisa, Zalfa; Ani Yuniarti, Falasifah; Lestari, Sri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Background: Babies with LBW are susceptible to medical complications, especially in breathing and heart. Immature lungs and heart affect oxygen saturation and pulse rate, so monitoring is needed to prevent serious complications. One complementary technique that can be used to maintain stable oxygen saturation and pulse rate is baby talk therapy and Al-Quran recitation. Research Method: The research method used is a case report using the intervention method. The study was conducted in the Peristi Tjitrowardojo Purworejo room, the research time was March 12-15, 2025. The research participants consisted of one neonatal patient with a diagnosis of LBW. Measurement of oxygen saturation and pulse rate was carried out before and after the intervention was given. Results: After the intervention of Talking to the baby for 5 minutes and Murotal Al-Qur'an Surat Ar-rahman for 30 minutes for four days showed an increase in oxygen saturation and a decrease in the baby's pulse rate. Conclusion: baby talking therapy and Murottal Al-Qur`an Surat Ar-Rahman have positive effects on oxygen saturation and pulse rate in patients with LBW.